Rapid cortical auditory evoked potentials audiometry. - Guyonnet-Hencke, T.; Portoles, O.; de Vries, M.; Koderman, E.; Winkler, A.; Goodall, J.; Desain, P.; Thielen, J.; Schulte, M.; Beynon, A. J.; van Kesteren, M. (International Journal of Audiology, 2025)
Objective: The current 'gold standard' of audiometry relies on subjective behavioural responses, which is impractical and unreliable for certain groups such as children, individuals with severe disabilities, or the disabled elderly. This study aims to validating blindly a novel electroencephalography (EEG) technique to estimate audiometric thresholds quickly. Design: Air-conduction audiometric thresholds at 250, 500, 1000, 2000, 4000, and 8000 Hz at 5 dB resolution were measured using three different systems: the novel EEG system, conventional pure-tone audiometry (PTA), and an automated behavioural test with the same stimulus properties as in the EEG test. EEG data were collected for 15 min from 32 semi-dry EEG electrodes. Later, the EEG system was trimmed to 8 electrodes and 7.5 min of data with satisfactory results. EEG and PTA thresholds were estimated blindly. Study sample: Audiometric thresholds were estimated from 10 elderly patients with asymmetric sensorineural hearing loss and five normal hearing young adults at both ears. Results: Correlation and regression analysis validated the hearing thresholds derived from both EEG configurations relative to the behavioural hearing thresholds – Spearman's correlation of 0.78 between PTA and 8-electrode 7.5-min EEG data. Conclusions: The results of this study open the door to rapid and objective hearing threshold estimation with EEG.